Eddy current loss behavior of hollow circular cylinder due to time varying electro-magnetic field - B B Balpande; G. D. Kedar; J. L. Matlam (International Journal of Applied Mechanics and Engineering, 2025)
The purpose of this study is to investigate the effects of a time-varying electromagnetic field on the quasi-static thermoelastic behavior of a finitely conducting hollow circular cylinder. As a consequence of a time-varying electromagnetic field, conducting currents, also known as eddy currents, are induced inside the cylinder. We treat the Joule heat that the induced eddy currents generate due to resistive heating as a thermal loading of the cylinder. The cylinder thickness is considered negligible in comparison to the magnetic field's penetration depth, and the problem is considered one-dimensional. The convection-type boundary conditions are applied across the curved surface of the cylinder. The intensity of Joule heat in terms of current density and eddy current loss is obtained in quasi-static form using integral transform techniques, which include the finite Hankel transform, the Marchi Zgrablich transform, and the Laplace transform. The quasi-static solutions of thermal stresses, displacement, non-dimensional temperature, eddy current loss, and magnetic field fluctuations are obtained in terms of electrical conductivity, magnetic permeability, frequency, and magnetic intensity of the electromagnetic field applied and are illustrated graphically using MATLAB software.